Penerapan Hukum Waris Secara Hibrida dalam Putusan Hakim yang Membatalkan Hibah Wasiat: Studi Putusan Nomor 2665 K/Pdt/2019 - Arief Zulkifli Nst; hasim purba; Henry Sinaga (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
A testamentary gift (legaat) is a specific provision within a will involving the bequest of one or more items of a particular type, or the granting of a right of usufruct (vruchtgebruik) over all or part of the estate. In the case at hand, the validity of a testamentary gift made by a Batak Toba testator to the youngest son (siampudan) from his second marriage is challenged by heirs from his first marriage. Legal complexity arises when judges within the general court system– adjudicating disputes regarding testamentary gifts made by Protestant Christian testators–invalidate such gifts and apply the one-third (1/3) testamentary limit that prevails in the religious court system. Using case, statutory and conceptual approaches, this research finds judicial inconsistency harming legitimaries and identifies teleological-sociological interpretation in situations where applicable law is already clear.